Biomineralization: Functions of calmodulin-like protein in the shell formation of pearl oyster - Yan, Zhenguang; Fang, Zi; Ma, Zhuojun; Deng, Jinye; Li, Shuo; Xie, Liping; Zhang, Rongqing (Biochimica et biophysica acta, 2007)
Calmodulin-like protein (CaLP) was believed to be involved in the shell formation of pearl oyster. However, no further study of this protein was ever performed. In this study, the in vitro crystallization experiment showed that CaLP can modify the morphology of calcite. In addition, aragonite crystals can be induced in the mixture of CaLP and a nacre protein (at 16 kDa), which was detected and purified from the EDTA-soluble matrix of nacre. These results agreed with that of immunohistological staining in which CaLP was detected not only in the organic layer sandwiched between nacre (aragonite) and the prismatic layer (calcite), but also around the prisms of the prismatic layer. Take together, we concluded that (1) CaLP, as a component of the organic layer, can induce the nucleation of aragonite through binding with the 16-kDa protein, and (2) CaLP may regulate the growth of calcite in the prismatic layer.